Resuscitation during the pandemic: Optional obligation? or supererogation?. (June 2021) - Perkins, Jonathan; Hamilton, Mark; Canniff, Charlotte; Gannon, Craig; Illsley, Marianne; Murray, Paul; Scribbins, Kate; Stockwell, Martin; Wilson, Justin; Gallagher, Ann
This paper is a response to a recent BMJ Blog: 'The duty to treat: where do the limits lie?' Members of the Surrey Heartlands Integrated Care Service Clinical Ethics Group (CEG) reflected on arguments in the Blog in relation to resuscitation during the COVID-19 pandemic. Clinicians have had to contend with ever-changing and conflicting guidance from the Resuscitation Council UK and Public Health England regarding personal protective equipment (PPE) requirements in resuscitation situations. St John Ambulance had different guidance for first responders. The situation regarding resuscitation led the CEG to consider ethical aspects of health care professionals' responses to the need for resuscitation during COVID-19. Members agreed that professionals should, ideally, have the level of PPE required for an aerosol generating procedure. However, there was no consensus regarding professionals' duty to care when this is not available. On the one hand, it was agreed that the casualty/patient's interests regarding resuscitation should be prioritised due to professionals' contract with the public and professional privilege. On the other hand, risk thresholds were considered relevant to individual decision-making and professionals' duty to care. All agreed that decision-making should not be influenced by rewards or reprimands. It was agreed also that decisions to resuscitate should not be considered as moral heroism or supererogatory - regardless of PPE availability - but rather as 'minimally decent'. We agreed that it may be acceptable for professionals, with good reasons, to opt out of resuscitation attempts and these should be reflected on and discussed before the event.